Images of a lengthy war - Meyerson, Joel D. (United States Army in Vietnam, 1986)
Images of a Lengthy War makes available for study and reference some of the important photographs of the Vietnam War, accompanied by brief narrative. The volume covers the three decades of the Army₂s experience in Vietnam, from the early years of advice and support to the French government through active intervention with combat forces and gradual withdrawal. Many of the photographs were selected to show the complex nature of the war, in particular demands of conducting counterguerrilla operations while undertaking conventional campaigns against enemy regulars. While the focus of the work is the American military, policy decisions in Washington and political developments in Vietnam are also amply illustrated to place the war in context. As a unique form of evidence, the photographs are a valuable resource in recalling the look of Vietnam.